Percutaneous screw fixation of the pubic symphysis versus plate osteosynthesis: a biomechanical study. Issue 4 (21st December 2022) - O'Neill, David E.; Bradley, Hallie R.; Hull, Brandon; Pierce, William; Grewal, Ishvinder S.; Starr, Adam J.; Sathy, Ashoke
Abstract : Abstract: Objectives: To compare the stability of screw fixation with that of plate fixation for symphyseal injuries in a vertically unstable pelvic injury (AO/Tile 61-C1) associated with complete disruption of the sacroiliac joint and the pubic symphysis. Methods: Eight fourth-generation composite pelvis models with sacroiliac and pubic symphyseal disruption (Sawbones, Vashon Island, WA) underwent biomechanical testing simulating static single-leg stance. Four were fixed anteriorly with a symphyseal screw, and 4 with a symphyseal plate. All had single transsacral screw fixation posteriorly. Displacement and rotation were monitored at both sacroiliac joint and pubic symphysis. Results: There was no significant difference between the 2 groups for mean maximum force generated. There was no significant difference in net displacement at both sacroiliac joint and pubic symphysis. There was significantly less rotation but more displacement in the screw group in the Z -axis. The screw group showed increased stiffness compared with the plate group. Conclusions: This is the first biomechanical study to compare screw versus plate symphyseal fixation in a Tile C model. Our biomechanical model using anterior and posterior fixation demonstrates that symphyseal screws may be a viable alternative to classically described symphyseal plating.